PKM PEMBERIAN EDUKASI MENGENAI SEKOLAH RAMAH ANAK DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SMPN 3 PINRANG - Balkis, Syarifah; Shasliani, Shasliani; Zulfadli, Muhammad; Khaeruddin, Khaeruddin; Wati, Fitra Widya (Universitas Negeri Makassar, 2024)
Child Friendly Schools (SRA) is an educational approach that places children at the center of attention by ensuring a learning environment that is safe, comfortable, inclusive, and supports children's growth and development optimally. This not only aims to improve students' academic achievement, but also shapes students' positive character so that they become individuals with integrity, tolerance and responsibility. The formation of students' character through SRA is important because character is the foundation that forms a child's personality and morality. There are several things that are of concern in each school, especially at SMPN 3 Pinrang, namely: a safe and violence-free environment for the development of positive character, for example children grow up in a safe and supportive atmosphere, making it easier to develop characters such as courage, self-confidence and discipline. Respect for children's rights as a basis for character formation, for example: children learn to become individuals who have integrity and respect for others, character education is embedded in daily activities, children's participation in decision making, development of attitudes of tolerance and empathy through inclusive education, and teachers at SMPN 3 Pinrang are expected to be role models who transmit positive character to students, for example: children imitate the positive attitudes of their teachers, so that character values are more easily ingrained in them.